Methods to identify postnatal depression in primary care: an integrated evidence synthesis and value of information analysis - CE Hewitt; SM Gilbody; S Brealey; M Paulden; S Palmer; R Mann; J Green; J Morrell; M Barkham; K Light; D Richards (Health Technology Assessment, 2009)
Objectives: To provide an overview of methods to identify postnatal depression (PND) in primary care and to assess their validity, acceptability, clinical effectiveness and cost-effectiveness, to model estimates of cost, to assess whether any method meets UK National Screening Committee (NSC) criteria and to identify areas for future research. Data sources: Searches of 20 electronic databases (including MEDLINE, CINAHL, PsycINFO, EMBASE, CENTRAL, DARE and CDSR), forward citation searching, personal communication with authors and searching of reference lists. Review methods: A generalised linear mixed model approach to the bivariate meta-analysis was undertaken for the validation review with quality assessment using QUADAS. Within the acceptability review, a textual narrative approach was employed to synthesise qualitative and quantitative research evidence. For the clinical and cost-effectiveness reviews methods outlined by the Centre for Reviews and Dissemination and the Cochrane Collaboration were followed. Probabilistic models were developed to estimate the costs associated with different identification strategies. Results: The Edinburgh Postnatal Depression Scale (EPDS) was the most frequently explored instrument across all of the reviews. In terms of test performance, postnatally the EPDS performed reasonably well: sensitivity ranged from 0.60 (specificity 0.97) to 0.96 (specificity 0.45) for major depression only; from 0.31 (specificity 0.99) to 0.91 (specificity 0.67) for major or minor depression; and from 0.38 (specificity 0.99) to 0.86 (specificity 0.87) for any psychiatric disorder. Evidence from the acceptability review indicated that, in the majority of studies, the EPDS was acceptable to women and health-care professionals when women were forewarned of the process, when the EPDS was administered in the home, with due attention to training, with empathetic skills of the health visitor and due consideration to positive responses to question 10 about self-harm. Suggestive evidence from the clinical effectiveness review indicated that use of the EPDS, compared with usual care, may lead to reductions in the number of women with depression scores above a threshold. In the absence of existing cost-effectiveness studies of PND identification strategies, a decision-analytic model was developed. The results of the base-case analysis suggested that use of formal identification strategies did not appear to represent value for money, based on conventional thresholds of cost-effectiveness used in the NHS. However, the scenarios considered demonstrated that this conclusion was primarily driven by the costs of false positives assumed in the base-case model. Conclusions: In light of the results of our evidence synthesis and decision modelling we revisited the examination of PND screening against five of the NSC criteria. We found that the accepted criteria for a PND screening programme were not currently met. The evidence suggested that there is a simple, safe, precise and validated screening test, in principle a suitable cut-off level could be defined and that the test is acceptable to the population. Evidence surrounding clinical and cost-effectiveness of methods to identify PND is lacking.: Further research should aim to identify the optimal identification strategy, in terms of key psychometric properties for postnatal populations. In particular, research comparing the performance of the Whooley and help questions, the EPDS and a generic depression measure would be informative. It would also be informative to identify the natural history of PND over time and to identify the clinical effectiveness of the most valid and acceptable method to identify PND. Further research within a randomised controlled trial would provide robust estimates of the clinical effectiveness.